Geriatric Telepsychiatry A Clinician's Guide - Srinivasan, Shilpa; Glover, Juliet; Bouknight, James G.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book provides a basic introduction to telepsychiatry, including potential benefits and drawbacks of utilizing this treatment modality. The text discusses applications in academic, public, federal, and educational settings and suggests practical guidelines for implementing and maintaining a telepsychiatry program. As the elder population continues to grow over the next several decades, digital tools, including videoconferencing, will play a large role in meeting the needs of the elderly. Written by the leaders in geriatric telepsychiatry, this text is the first to focus on the psychiatric application of these digital tools, lay out the policies and guidelines for treating patients who can benefit from this service, and outline the most cutting-edge research on the topic. Geriatric Telepsychiatry is the ultimate guide for psychiatrists, geriatricians, social workers, geriatric nurses, students, long-term care facilitators, and all medical professionals who work with the elderly psychiatric patient. .
Introduction -- Overview of Telepsychiatry in Geriatrics -- Economics of Telehealth in Geriatric Psychiatry -- Geriatric Telepsychiatry in Academic Settings -- Administration of New Telepsychiatry Programs in Public Psychiatry and Applications in Geriatrics -- Gero-Telehealth in VA systems -- Scope of Geriatric Telepsychiatry in Clinical Settings -- Technology Applications and Implications for Implementation. .
Keywords: Medicine; Public health; Geriatrics; Psychiatry; Medical research; Practice of medicine; Quality of life; Medicine & Public Health; Psychiatry; Geriatrics/Gerontology.; Practice and Hospital Management; Public health; Quality of Life Research